Semi-solid mechanical stirring SiC reinforced Mg-Gd-Y-Ag-Zr magnesium alloy square bar and short process preparation method thereof

CN122918403APending Publication Date: 2026-10-16JIANGXI MAGNESIUM-BASED NEW MATERIALS IND APPLICATION RESEARCH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611134066.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0009]针对现有技术中Mg-Gd-Y-Ag-Zr系镁合金铸态组织粗大、后续加工工序繁琐、纳米SiC增强相难以工业化应用以及微米SiC在稀土镁合金熔体中分散困难等不足,本发明提供一种半固态机械搅拌高强Mg-Gd-Y-Ag-Zr镁合金方棒及其短流程制备方法

Benefits of technology

(1)本发明采用微米级SiC颗粒作为增强相,相比于纳米级SiC颗粒,微米级SiC颗粒比表面积小、表面活性低,不易发生团聚和氧化烧损,工艺稳定性强、成本低、可量产,规避了纳米颗粒增强相团聚、氧化、成本高的缺点,适于大规模工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918403A_ABST
    Figure CN122918403A_ABST
Patent Text Reader

Abstract

The application discloses a kind of semi-solid mechanical stirring high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bar and short process preparation method thereof, belong to magnesium alloy composite material preparation technical field.The magnesium alloy square bar is by the following components according to weight percentage:Gd 8.0-9.0%, Y 2.0-2.8%, Ag 1.5-2.0%, Zr 0.3-0.5%, SiC 0.3-0.8%, the balance is Mg and inevitable impurities.Its preparation method includes: batching smelting, SiC pre-oxidation treatment, semi-solid mechanical stirring, casting obtains semi-solid casting blank, two-stage solid solution and once extrusion forming.The application uses micron grade SiC particle as reinforcing phase, obtains uniform spherical semi-solid slurry by mechanical shearing stirring broken coarse dendrite in semi-solid temperature interval, combined with two-stage solid solution and once extrusion short process technology, the tensile strength of Mg-Gd-Y-Ag-Zr magnesium alloy square bar prepared can reach 438MPa, total elongation at break reaches 28.5%, with high strength and good plasticity, process flow is short, suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnesium alloy composite material preparation technology, and in particular to a semi-solid mechanically stirred high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bar and its short-process preparation method. Background Technology

[0003] This section provides only background information related to this application to enable those skilled in the art to understand this application more thoroughly and accurately, and it is not necessarily prior art.

[0004] Rare earth magnesium alloys are important lightweight materials in aerospace and high-end equipment fields due to their high specific strength, high specific stiffness and good high-temperature creep performance. Among them, Mg-Gd-Y-Ag-Zr alloys have become one of the mainstream systems of ultra-high strength magnesium alloys due to the synergistic strengthening of multiple rare earth elements and excellent comprehensive mechanical properties. For example, the tensile strength of Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr alloy prepared by Zhou Hao et al. by extrusion + artificial aging (T5 state) is 430MPa (Zhou Hao, Wang Qudong, Chen Jie, Ye Bing, Guo Wei. Microstructure and mechanical properties of extruded Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr alloy (English) [J]. Journal of China Nonferrous Metals Society, 2012, 22(8):1891-1895.).

[0005] Currently, research on Mg-Gd-Y-Ag-Zr magnesium alloys mainly suffers from the following shortcomings: First, most studies use traditional casting processes, resulting in coarse as-cast structures and uneven composition. Subsequent modifications are difficult to completely eliminate defects such as casting shrinkage and segregation, which restricts further improvement of the alloy's mechanical properties.

[0006] Secondly, the forming process mainly involves low-temperature multi-pass extrusion at 350℃ and below, and sheet rolling. The process is complicated, has high residual stress, and cannot meet the requirements for the preparation of solid load-bearing components such as square bars.

[0007] Third, most studies focus on optimizing alloy composition, while systematic research on the coupling of particle-reinforcing phases and precise processes is limited, making it difficult to further improve the strength of the alloy. SiC ceramic particles, with their advantages of high hardness, high modulus, good thermal stability, and excellent compatibility with the magnesium matrix, are the most commonly used reinforcing phase in magnesium alloys. Current domestic and international research mainly focuses on nanoscale SiC particle reinforcement. However, while nanoparticles have a large specific surface area and high surface activity, and possess a certain grain refinement effect, they are prone to agglomeration and oxidation burn-off. Furthermore, the preparation process is complex, the cost of nanoparticles is high, and their stability is poor, making large-scale industrial production difficult.

[0008] Semi-solid mechanical stirring is a low-cost preparation process for particle-reinforced magnesium matrix composites. It utilizes mechanical shearing and stirring in the solid-liquid two-phase region of the alloy to break up coarse initial grains and obtain a uniform spherical semi-solid slurry. This eliminates casting shrinkage and segregation defects at the source, while retaining the skeletal support of the solid particles, providing a good billet for subsequent plastic forming. However, high-rare-earth Mg-Gd-Y-Ag-Zr magnesium alloy melts have high viscosity and strong surface activity. Direct doping with micron-sized SiC easily leads to localized sedimentation and interfacial voids. Improving the wettability between SiC and the magnesium matrix and achieving uniform dispersion of SiC particles are key technical challenges in the preparation of this type of composite material. Summary of the Invention

[0009] To address the shortcomings of existing technologies, such as the coarse as-cast microstructure of Mg-Gd-Y-Ag-Zr magnesium alloys, cumbersome subsequent processing steps, difficulty in industrial application of nano-SiC reinforcing phases, and difficulty in dispersing micron-sized SiC in rare earth magnesium alloy melts, this invention provides a semi-solid mechanically stirred high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bar and its short-process preparation method.

[0010] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A semi-solid mechanically stirred high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bar, composed of the following components by weight percentage: Gd 8.0-9.0%, Y 2.0-2.8%, Ag 1.5-2.0%, Zr 0.3-0.5%, SiC 0.3-0.8%, balance Mg and unavoidable impurities.

[0011] Preferably, the particle size of the SiC is 1-2 μm.

[0012] The above-mentioned short-process preparation method for semi-solid mechanically stirred high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bars includes the following steps: (1) Batching and smelting: Magnesium ingots, Mg-Gd master alloy, Mg-Y master alloy, pure Ag particles and Mg-Zr master alloy are used as raw materials. After drying, they are smelted under a protective atmosphere to obtain Mg-Gd-Y-Ag-Zr magnesium alloy melt. (2) SiC pre-oxidation treatment: SiC particles are pre-oxidized; (3) Semi-solid mechanical stirring: Cool the magnesium alloy melt obtained in step (1) to the semi-solid temperature range, add the SiC particles after the pre-oxidation treatment in step (2), use a stirrer for mechanical stirring, remove the slag and cast to obtain a semi-solid billet. (4) Solution treatment: The semi-solid casting obtained in step (3) is subjected to solution treatment to remove surface oxides; (5) Extrusion molding: The billet obtained in step (4) is heated and then extruded to obtain magnesium alloy square bars.

[0013] Preferably, the magnesium ingot in step (1) is a magnesium ingot with a purity of 99.99%, the pure Ag particles are pure Ag particles with a purity of 99.99%, the Mg-Gd master alloy is a Mg-25Gd master alloy, the Mg-Y master alloy is a Mg-20Y master alloy, and the Mg-Zr master alloy is a Mg-30Zr master alloy.

[0014] Preferably, the drying temperature in step (1) is 200°C, the drying time is 2 hours, the protective atmosphere is SF6+CO2, and the melting temperature is 720-740°C.

[0015] Preferably, the pre-oxidation treatment in step (2) is pre-oxidation at 700°C for 2-3 hours.

[0016] Preferably, the semi-solid temperature range in step (3) is 568-588℃, which corresponds to a solid fraction of 40%-60% for the Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr alloy.

[0017] Preferably, the stirrer in step (3) is an upward-pushing 60° inclined blade stirrer with a stirring speed of 200-500 r / min and a stirring time of 15-40 min.

[0018] Preferably, the solution treatment in step (4) is a two-stage solution treatment. The specific process is as follows: first, keep the sample at 420℃ for 4 hours, then heat it to 500℃ in the furnace and keep it at 500℃ for 12 hours, then air cool it and quench it with water. After water quenching, the homogenized sample is machined to remove surface oxides.

[0019] Preferably, the extrusion process parameters in step (5) are: extrusion temperature 420℃, holding time 1h, extrusion speed 0.6mm / s, and extrusion ratio 23:1.

[0020] Compared with the prior art, the present invention has the following advantages: (1) The present invention uses micron-sized SiC particles as the reinforcing phase. Compared with nano-sized SiC particles, micron-sized SiC particles have a smaller specific surface area and lower surface activity, making them less prone to agglomeration and oxidation. They have strong process stability, low cost, and can be mass-produced, thus avoiding the disadvantages of agglomeration, oxidation, and high cost of nano-particle reinforcing phases. They are suitable for large-scale industrial production.

[0021] (2) This invention addresses the technical challenges of high melt viscosity, strong surface activity, and easy local sedimentation and interfacial voids in high rare earth Mg-Gd-Y-Ag-Zr magnesium alloys, and the direct doping of micron-sized SiC. It proposes a core process of SiC pre-oxidation treatment (pre-oxidation at 700℃ for 2-3 hours), which effectively improves the wetting performance between SiC particles and the magnesium matrix. At the same time, combined with a semi-solid mechanical stirring process, within the optimal stirring range of 568-588℃ (corresponding to a solid fraction of 40%-60%), coarse dendrites are efficiently broken by mechanical shearing to obtain a uniform spherical semi-solid slurry. This eliminates casting shrinkage and segregation defects from the source, while avoiding the sedimentation and floating of micron-sized SiC particles, thus balancing the grain spheroidization effect and the uniformity of particle dispersion.

[0022] (3) This invention adopts a one-time extrusion molding process, eliminating the need for multiple extrusion, rolling, or aging treatments. The process is short, easy to operate, and has low residual stress, enabling the efficient preparation of high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bars. This superimposed process framework has good process window adaptability, achieving excellent comprehensive mechanical properties within a wide range of parameter variations. Testing shows that the Mg-Gd-Y-Ag-Zr magnesium alloy square bars prepared by this invention have a tensile strength of 424-438 MPa and a total elongation at break of 21.1%-28.5%, exhibiting both high strength and good plasticity, with excellent comprehensive mechanical properties.

[0023] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 This is a true stress-true strain curve of the sample in Example 1 of this invention at room temperature under tension; Figure 2 This is a true stress-true strain curve of the sample in Example 2 of this invention at room temperature under tension. Figure 3 This is a true stress-true strain curve of the sample in Example 3 of this invention under room temperature tensile stress. Detailed Implementation

[0026] It should be understood that the process parameters described in the following specific embodiments (including but not limited to melting temperature, pre-oxidation temperature and time, stirring temperature range, stirring speed and time, solution temperature and time, extrusion temperature and extrusion ratio, etc.) are preferred embodiments under the specific alloy system of this invention. Those skilled in the art can reasonably adjust the specific parameters within the above-mentioned higher-level process framework according to the actual alloy composition, equipment conditions and target product size. As long as they do not deviate from the core technical concept of semi-solid mechanical stirring + short-process one-time extrusion molding, they are all within the protection scope of this invention.

[0027] Example 1 This embodiment provides a semi-solid mechanically stirred high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bar and its short-process preparation method.

[0028] 1. Alloy composition By weight percentage, the composition of the magnesium alloy square bar in this embodiment is: Gd 8.5%, Y 2.3%, Ag 1.8%, Zr 0.4%, SiC 0.3%, with the balance being Mg and unavoidable impurities. The SiC particle size is 1-2 μm.

[0029] II. Preparation Method Within the framework of the above-described superposition preparation method, the preferred process parameters used in this embodiment are as follows: (1) Batching and smelting The base alloy raw materials were selected as follows: magnesium ingots with a purity of 99.99%, Mg-25Gd master alloy, Mg-20Y master alloy, pure Ag particles with a purity of 99.99%, and Mg-30Zr master alloy. The magnesium ingots, pure Ag particles, and master alloys were all dried in a box furnace at 200℃ for 2 hours to remove surface moisture and oil, preventing oxidation during high-temperature melting of the rare earth magnesium alloy and ensuring the purity of the slurry.

[0030] After the dried raw materials are weighed according to the formula, they are smelted at 720-740℃ under the SF6+CO2 protective atmosphere to obtain Mg-Gd-Y-Ag-Zr magnesium alloy melt.

[0031] (2) SiC pre-oxidation treatment SiC particles with a diameter of 1-2 μm were pre-oxidized at 700℃ for 2-3 hours. This pre-oxidation treatment is a core and critical process. Due to the high viscosity and strong surface activity of high rare earth Mg-Gd-Y-Ag-Zr magnesium alloy melt, direct doping of micron-sized SiC is prone to local sedimentation and interfacial voids. The pre-oxidation treatment can form a SiO2 oxide layer on the surface of SiC particles, effectively improving the wetting performance between SiC particles and the magnesium matrix, laying the foundation for subsequent uniform dispersion.

[0032] (3) Semi-solid mechanical stirring Based on the solid-liquid phase temperature characteristics of the Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr alloy (liquidite approximately 610-630℃, solidus approximately 500-525℃), 568-588℃ was selected as the semi-solid stirring temperature range. This temperature range corresponds to a solid fraction of 40%-60%, which is the optimal stirring range. Within this range, the primary rare earth Mg-(Gd,Y) phase is in a semi-molten state, and mechanical shearing can efficiently break up coarse dendrites while retaining a suitable solid framework, preventing the sedimentation and floating of micron-sized SiC particles, and balancing grain spheroidization and particle dispersion uniformity.

[0033] The magnesium alloy melt obtained in step (1) is cooled to 568-588℃, and the SiC particles pre-oxidized in step (2) are added. The mixture is stirred for 15-40 minutes at a speed of 200-500 r / min using an upward-push 60° inclined blade agitator. After slag removal, the mixture is cast to obtain a semi-solid billet. The upward-push 60° inclined blade agitator refers to an agitator in which the blades are installed at a 60° angle to the axis of the stirring shaft and drive the slurry to flow upward along the axial direction during stirring.

[0034] (4) Two-stage solution treatment A two-stage solution treatment process was adopted: the semi-solid casting obtained in step (3) was first kept at 420℃ for 4 hours, and then the temperature was raised to 500℃ and kept for 12 hours. After air cooling for a period of time, it was water quenched. The homogenized sample was then surface-machined to remove surface oxides.

[0035] (5) One-time extrusion molding The billet obtained in step (4) is heated to 420°C and held for 1 hour. It is then extruded once at an extrusion speed of 0.6 mm / s and an extrusion ratio of 23:1 to obtain a magnesium alloy square bar with an outer dimension of 11×11 mm.

[0036] III. Performance Testing The tensile strength of the Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr-0.3SiC magnesium alloy square bar sample prepared in this embodiment was 435 MPa, and the total elongation at break was 25.1%.

[0037] Example 2 This embodiment provides a semi-solid mechanically stirred high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bar and its short-process preparation method.

[0038] 1. Alloy composition By weight percentage, the composition of the magnesium alloy square bar in this embodiment is: Gd 8.5%, Y 2.3%, Ag 1.8%, Zr 0.4%, SiC 0.5%, with the balance being Mg and unavoidable impurities. The SiC particle size is 1-2 μm.

[0039] II. Preparation Method The preparation method of this embodiment is basically the same as that of Example 1, except that the amount of SiC added is different. Other preferred process parameters (including melting temperature, pre-oxidation conditions, semi-solid stirring temperature and time, two-stage solid solution process, extrusion parameters, etc.) are consistent with those of Example 1.

[0040] Specifically: (1) Batching and smelting: Weigh the raw materials according to the composition ratio of Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr-0.5SiC, dry them at 200℃ for 2h, and then smelt them at 720-740℃ under the protective atmosphere of SF6+CO2.

[0041] (2) SiC pre-oxidation treatment: SiC particles with a particle size of 1-2 μm are pre-oxidized at 700℃ for 2-3 h.

[0042] (3) Semi-solid mechanical stirring: Cool the magnesium alloy melt to 568-588℃, add pre-oxidized SiC particles, stir with a 60° inclined blade stirrer at a speed of 200-500r / min for 15-40min, remove slag and cast to obtain a semi-solid billet.

[0043] (4) Two-stage solution treatment: The semi-solid billet was held at 420℃ for 4 hours, then heated to 500℃ and held for 12 hours in the furnace, and then air-cooled for a period of time before water quenching. The homogenized sample was then surface-machined to remove surface oxides.

[0044] (5) One-time extrusion molding: The billet is heated to 420℃ and held for 1 hour. The extrusion speed is 0.6 mm / s and the extrusion ratio is 23:1 to obtain 11×11 mm square bars.

[0045] III. Performance Testing According to the test results, the tensile strength of the Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr-0.5SiC magnesium alloy square bar sample prepared in this embodiment is 438MPa, and the total elongation at break is 28.5%.

[0046] In this embodiment, the SiC content is 0.5%. When the SiC content is low, the proportion of rare earth elements consumed in the reaction with Gd / Y is small, resulting in a smaller weakening effect on strength. Precipitation strengthening and heterogeneous nucleation refinement play a dominant role, thus leading to higher strength. At the same time, the appropriate amount of SiC addition is beneficial to improving the plasticity of the alloy, and the elongation reaches the optimal value of 28.5%.

[0047] Example 3 This embodiment provides a semi-solid mechanically stirred high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bar and its short-process preparation method.

[0048] 1. Alloy composition By weight percentage, the composition of the magnesium alloy square bar in this embodiment is: Gd 8.5%, Y 2.3%, Ag 1.8%, Zr 0.4%, SiC 0.8%, with the balance being Mg and unavoidable impurities. The SiC particle size is 1-2 μm.

[0049] II. Preparation Method The preparation method of this embodiment is basically the same as that of Examples 1 and 2, except that the amount of SiC added is different (0.8%), while other preferred process parameters remain the same.

[0050] III. Performance Testing The tensile strength of the Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr-0.8SiC magnesium alloy square bar sample prepared in this embodiment was 424 MPa, and the total elongation at break was 21.1%.

[0051] When the SiC content increases to 0.8%, the rare earth elements consumed in the reaction between SiC and Gd / Y increase significantly, affecting the supersaturation of the alloy and leading to a decrease in the density of the γ″ strengthening phase and a reduction in strength (424 MPa). Simultaneously, with the increase in SiC content, the reaction generates submicron to micron-sized brittle phases mainly distributed at grain boundaries. During tensile testing, these brittle phases become stress concentration sources, reducing elongation (21.1%).

[0052] Comprehensive comparison of Examples 1-3 The room temperature tensile properties of Examples 1-3 are summarized in the table below: From the above results, we can conclude that: With the increase of the content of micron-sized SiC particles, the strength showed a trend of first slightly increasing and then decreasing (435MPa→438MPa→424MPa), while the elongation showed a trend of first increasing and then decreasing (25.1%→28.5%→21.1%). Overall, Example 2 (SiC content 0.5%) showed the best comprehensive mechanical properties, with a tensile strength of 438MPa and a total elongation at break of 28.5%.

[0053] In Examples 1 and 2, the amount of SiC added was relatively small, and the proportion of rare earth elements consumed in the reaction with Gd / Y was relatively small, resulting in a smaller weakening effect on strength. The strengthening effect of precipitated phase and the refinement of heterogeneous nucleation played a dominant role, thus resulting in higher strength. However, after the addition of 0.8% SiC, the rare earth elements consumed in the reaction with Gd / Y significantly affected the supersaturation of the alloy, and the density of the γ″ strengthening phase decreased, leading to a slight decrease in strength.

[0054] As the SiC content increases, the reaction generates submicron to micron-sized brittle phases mainly distributed at the grain boundaries. During stretching, these brittle phases become stress concentration sources, reducing the elongation.

[0055] This invention employs a single extrusion molding process. The lower extrusion speed helps ensure the stability of the extrusion process and the dimensional accuracy of the square bar. The appropriate extrusion ratio ensures sufficient deformation and fragmentation of the as-cast structure while avoiding excessive mold load and product cracking risks caused by an excessively high extrusion ratio. By using only a single extrusion molding process, there is no need for multiple extrusion, rolling, or aging treatments, which significantly shortens the process flow, improves production efficiency, and reduces production costs.

[0056] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

[0057] For those skilled in the art, various changes and modifications will undoubtedly be apparent after reading the above description. Therefore, the appended claims should be construed as covering all changes and modifications that encompass the true intent and scope of the invention. Any and all equivalent scope and content within the scope of the claims should be considered to remain within the intent and scope of the invention.

Claims

1. A semi-solid mechanically stirred high-strength Mg-Gd-Y-Ag-Zr magnesium alloy square bar, characterized in that, It consists of the following components by weight percentage: Gd 8.0-9.0%; Y 2.0-2.8%; Ag 1.5-2.0%; Zr 0.3-0.5%; SiC 0.3-0.8%; The balance is Mg and unavoidable impurities.

2. The magnesium alloy square bar according to claim 1, characterized in that: The SiC has a particle size of 1-2 μm.

3. A short-process preparation method for magnesium alloy square bars as described in claim 1 or 2, characterized in that, Includes the following steps: (1) Batching and smelting: Magnesium ingots, Mg-Gd master alloy, Mg-Y master alloy, pure Ag particles and Mg-Zr master alloy are used as raw materials. After drying, they are smelted under a protective atmosphere to obtain Mg-Gd-Y-Ag-Zr magnesium alloy melt. (2) SiC pre-oxidation treatment: SiC particles are pre-oxidized; (3) Semi-solid mechanical stirring: Cool the magnesium alloy melt obtained in step (1) to the semi-solid temperature range, add the SiC particles after the pre-oxidation treatment in step (2), use a stirrer for mechanical stirring, remove the slag and cast to obtain a semi-solid billet. (4) Solution treatment: The semi-solid casting obtained in step (3) is subjected to solution treatment to remove surface oxides; (5) Extrusion molding: The billet obtained in step (4) is heated and then extruded to obtain magnesium alloy square bars.

4. The short-process preparation method according to claim 3, characterized in that: The magnesium ingot mentioned in step (1) is a magnesium ingot with a purity of 99.99%, the pure Ag particles are pure Ag particles with a purity of 99.99%, the Mg-Gd master alloy is a Mg-25Gd master alloy, the Mg-Y master alloy is a Mg-20Y master alloy, and the Mg-Zr master alloy is a Mg-30Zr master alloy.

5. The short-process preparation method according to claim 3, characterized in that: The drying temperature in step (1) is 200℃, the drying time is 2h, the protective atmosphere is SF6+CO2, and the melting temperature is 720-740℃.

6. The short-process preparation method according to claim 3, characterized in that: The pre-oxidation treatment in step (2) is to pre-oxidize at 700℃ for 2-3 hours.

7. The short-process preparation method according to claim 3, characterized in that: The semi-solid temperature range mentioned in step (3) is 568-588℃, which corresponds to a solid fraction of 40%-60% for the Mg-8.5Gd-2.3Y-1.8Ag-0.4Zr alloy.

8. The short-process preparation method according to claim 3, characterized in that: The stirrer mentioned in step (3) is a push-type 60° inclined blade stirrer with a stirring speed of 200-500 r / min and a stirring time of 15-40 min.

9. According to the short-process preparation method of claim 3, the solid solution treatment in step (4) is a two-stage solid solution treatment. The specific process is as follows: first, keep the sample at 420℃ for 4 hours, then heat it to 500℃ with the furnace and keep it at 500℃ for 12 hours, then air cool it and quench it with water. After water quenching, the homogenized sample is machined to remove surface oxides.

10. The short-process preparation method according to claim 3, characterized in that: The extrusion process parameters in step (5) are: extrusion temperature 420℃, holding time 1h, extrusion speed 0.6mm / s, and extrusion ratio 23:1.